Excel by example a Microsoft Excel cookbook for electronics engineers - Kagan, Aubrey (Amsterdam ; Boston : Elsevier/Newnes, 2004)
The spreadsheet has become a ubiquitous engineering tool, and Microsoft Excel is the standard spreadsheet software package. Over the years, Excel has become such a complex program that most engineers understand and use only a tiny part of its power and features. This book is aimed at electronics engineers and technicians in particular, showing them how to best use Excel's features for computations, circuit modeling, graphing, and data analysis as applied to electronics design. Separate chapters cover lookup tables and file I/O, using macros, graphing, controls, using Analysis Toolpak for statistical analysis, databases, and linking into Excel from other sources, such as data from a serial port. The book is basically an engineering cookbook, with each chapter providing tutorial information along with several Excel "recipes" of interest to electronics engineers. The accompanying CD-ROM features ready-to-run, customizable Excel worksheets derived from the book examples, which will be useful tools to add to any electronics engineer's spreadsheet toolbox. Engineers are looking for any and all means to increase their efficiency and add to their "bag of design tricks." Just about every electronics engineer uses Excel but most feel that the program has many more features to offer, if they only knew what they were! The Excel documentation is voluminous and electronics engineers don't have the time to read it all and sift through looking for those features that are directly applicable to their jobs and figure out how to use them. This book does that task for them-pulls out those features that they need to know about and shows them how to make use of them in specific design examples that they can then tailor to their own design needs. *This is the ONLY book to deal with Excel specifically in the electronics field *Distills voluminous and time-consuming Excel documentation down to nitty-gritty explanations of those features that are directly applicable to the electronics engineer's daily job duties *The accompanying CD-ROM provides ready-to-use, fully-customizable worksheets from the book's examples.
Introduction -- Excel Basics: -- -- autofill -- -- copying formulae -- -- relative & absolute -- -- naming cells -- -- formatting cells -- -- simple examples- amplifiers -- LookupTables, File I/O (comma delimited): -- -- price break table -- -- interface to Parts & Vendors -- -- MTBF calculation -- Macros -- -- Resistor value -- -- Timer -- -- Best Resistor pair selection -- -- Voltage regulator model -- -- 555 timer -- -- XTR104 model -- -- Automatic open -- -- Goal seek -- -- Timer -- -- Solver -- Graphs -- -- curve fitting -- -- Bode plots -- -- Polar plots -- -- Simulating input/ monitor and plot output for a digital PID loop -- -- non-linear response -- -- -- Controls -- -- pushbuttons -- -- hex<-> decimal conversion -- -- LCD initialization application -- -- Spinners -- -- Generate initialization code for microcomputer (e.g. 8051) -- -- Serial number generation (or P.O. number etc.) -- -- Hide Excel from view -- Voice control of Excel -- Analysis Toolpak- statistical analysis -- -- moving average -- -- random number generation -- -- Fourier analysis -- Data base -- -- sort bills of material -- External input into Excel -- -- linking to other applications, copying, dynamic updating -- -- loading files -- -- Enter data from serial port into spreadsheet -- -- Invoke Excel from Visual Basic -- Other resources -- Index.
Includes bibliographical references (p. 354-356) and index.
Keywords: Electrical engineering -- Data processing; Microsoft Excel (Computer file).; Electronic books